2021
DOI: 10.3390/ma14112793
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Impact of Building Materials in Residential Buildings in Turkey

Abstract: In Turkey, heat loss from existing and new buildings constitutes a large part of energy waste, so usage of suitable construction material is quite important. The building selected in this study was analyzed by applying different building materials considering the annual energy consumption allowed, and according to the different heat zones and different thicknesses of insulation material in relation to demand. The most suitable building material in terms of energy and cost uptake and cost given to the regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Buildings, as the major energy consumer in urban areas 1 , have the highest energy-saving potential. To promote building energy efficiency, building energy simulation is a powerful tool to identify proper energy-saving solutions, such as using alternative construction materials 2 and improving energy management systems 3 . In the context of the city environment, the simulation approach is a significant decision-making reference for local governors and city managers.…”
Section: Background and Summarymentioning
confidence: 99%
“…Buildings, as the major energy consumer in urban areas 1 , have the highest energy-saving potential. To promote building energy efficiency, building energy simulation is a powerful tool to identify proper energy-saving solutions, such as using alternative construction materials 2 and improving energy management systems 3 . In the context of the city environment, the simulation approach is a significant decision-making reference for local governors and city managers.…”
Section: Background and Summarymentioning
confidence: 99%
“…Despite, residential buildings were highly subjected to the studies performed in the assessment of the energy efficiency, office or public buildings and schools were not common in the literature to compare the improvement of energy loss according to the methods and measures applied to the buildings. When the energy requirement of the three story residential building was calculated with varying the wall type materials as horizontal perforated brick, pumice block and aerated concrete block with carrying out of expanded polystyrene insulation material to the external walls in the third region of climate zone of Turkish standard 825, it was detected that application of insulation to the aerated concrete wall type led to more expensive result than other systems in the third region of climate zone [10]. However, energy performance of a primary school project examined in Ankara located at third region of climate zones for Turkey according to Turkish standard 825 was improved only 4.09 % with various passive strategies such as window-to-wall ratios, wall and glazing materials, insulation thickness [11].…”
Section: State Of the Artmentioning
confidence: 99%
“…It was determined that the aerated concrete block wall provided 2.8 % less cost in total without requiring thermal insulation material on the first‐ and second‐degree zones while aerated concrete block wall and insulation material were imparting 0.36 % more expensive result than other systems in the third‐degree zone. However, the application of 10 cm thick expanded polystyrene insulation material on the wall layers in the fourth‐degree zone could not provide the Turkish standard 825 limit values for the brick and pumice systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with emphasis on architectural heritage conservation and construction development, a variety of scholars have focused on examining regional and local rural development [26,27]. Wang et al [28] revealed that the expression of intangible cultural elements in residential architectural heritage was insufficient among the current world heritage sites, and put forward architectural landscape protection and inheritance coping strategies based on the principle of authenticity.…”
Section: Introductionmentioning
confidence: 99%